EFFECT OF IRRIGATION INTERVALS ON THE QUALITY AND STORAGE PERFORMANCE OF STRAWBERRY FRUIT - I. Akhtar; A. Rab (Journal of Animal and Plant Sciences, 2015)
The effect of irrigation intervals on the quality and storage performance of strawberry fruit was investigated at district Charsadda during the vegetation period 2010/2011.The strawberry (cv. 'Chandler') fruits, harvested from plots irrigated at 4, 6, 8, 10, 12 and 14 days interval were analyzed for physico-chemical characteristics immediately at harvest and after 8 days storage at 5±2°C and 90% relative humidity (RH) in perforated plastic packages. Irrigation intervals significantly affected the fruit quality and storage performance. The maximum fresh fruit weight (11.84 g), moisture content (86.35%) and ascorbic acid content (58.67 mg/100g), recorded with 4 days irrigation interval. Such features declined with increasing irrigation intervals to 14 days to the minimum fruit weight (7.91 g), moisture content (80.04%) and ascorbic acid (38.15 mg/100 g). By contrast, reducing sugars (6.31%), non-reducing sugar (2.01%), total sugars (8.32%), and titratable acidity (1.51%) were highest with 8 days irrigation interval and the highest total soluble solids (9.04%) and organoleptic quality score (8.00) were recorded with 10 days irrigation interval. The storage performance as determined by disease incidence, marketable fruits and shelf life revealed that disease incidence was not significantly affected by irrigation interval and storage but the maximum marketable fruits (95.25%) and shelf life (9.00 days) were recorded with 10 days irrigation interval. The interaction of irrigation interval and storage also significantly affected the fruit quality. The highest (7.26%) reducing sugars was recorded with the interaction of 12 days irrigation interval and 8 days storage, followed by 7.08% with the difference being non-significant recorded with the interaction of 10 days irrigation interval and 8 days storage, the highest TSS (9.37%) and total sugars (8.79%) were recorded with 10 days irrigation interval and 8 days storage. It can be concluded that while 4 days irrigation interval may be optimum for fresh fruit consumption, irrigation interval of 10 days is appropriate for retaining quality during storage or distant marketing.
Keywords: Fruit; Irrigation Intervals; Quality; Strawberry; Storage; Sugars; TSS